2023
DOI: 10.3390/jpm13081206
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Non-Adherence to Allergen-Specific Immunotherapy: A Foundation towards a Patient-Personalized Approach

Erminia Ridolo,
Francesca Nicoletta,
Alessandro Barone
et al.

Abstract: Background. Allergen-specific immunotherapy (AIT) is the only disease-modifying therapy for allergic conditions, resulting in a long-lasting tolerance beyond the duration of the treatment. Due to the strong relationship between the effectiveness, its optimal duration (at least three years) and the observation of the correct administration protocol, appropriate adherence to the plan of treatment represents a critical factor for the therapeutical success of AIT. Methods. Analysis of studies about the rate of adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Current guidelines recommend that AIT can be initiated at 5 years of age [34]; meanwhile, allergen sensitization can start as early as 12 months of age [35]. In this regard, a comprehensive individual patient selection process, including the sensitization profile related to the current allergen exposome, the active underlying atopic disease, and associated comorbidities, increases the adherence to prescribed medications and the success of AIT [36]. Despite previous studies having confirmed that PAMD@ changed the choice of relevant allergens for allergen-specific immunotherapy in at least 50% of cases [37,38], further investigations are warranted to investigate the prophylactic role of AIT in these patients with a clinically relevant sensitization under the age of 5 years old before the development of complete longitudinal mite sensitization trajectories.…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines recommend that AIT can be initiated at 5 years of age [34]; meanwhile, allergen sensitization can start as early as 12 months of age [35]. In this regard, a comprehensive individual patient selection process, including the sensitization profile related to the current allergen exposome, the active underlying atopic disease, and associated comorbidities, increases the adherence to prescribed medications and the success of AIT [36]. Despite previous studies having confirmed that PAMD@ changed the choice of relevant allergens for allergen-specific immunotherapy in at least 50% of cases [37,38], further investigations are warranted to investigate the prophylactic role of AIT in these patients with a clinically relevant sensitization under the age of 5 years old before the development of complete longitudinal mite sensitization trajectories.…”
Section: Discussionmentioning
confidence: 99%